(untitled) (Tabularium Historiae, 2018)
The Potulicki family was owner of huge manor in former Nakło county. In Więcbork, a headquarter of Potulicki family are two tombstones from 18th century with Latin epitaphs. At the end of century part of the family settled in Potulice near Nakło town. The church built there was treated as mausoleum. Decedents were buried in this church underground from half of 19th century to 1932. Essential information about them is contained on tombstones covering their graves. Two of tombstones located in the church have inscriptions in Latin. Next gravestones with Polish epitaphs are hidden underground. Letters are scrupulously sculpted in stone and paint filled. Width of several centimeters high letters depends on text length. All tombstone inscriptions are all caps texts and contain common abbreviations and acronyms.